EFFECT OF INDIGENOUSLY ISOLATED SACCHAROMYCES CEREVISIAE PROBIOTICS ON MILK PRODUCTION, NUTRIENT DIGESTIBILITY, BLOOD CHEMISTRY AND FECAL MICROBIOTA IN LACTATING DAIRY COWS - G. Shakira M. Qubtia; I. Ahmed; F. Hasan; M. I. Anjum; M. Imran (Journal of Animal and Plant Sciences, 2018)
Inadequate and unbalanced diet is considered a major constraint for livestock promotion in developing countries which leads to disturbance in ruminal gut microbial flora. Ruminal gut microbes play a vital role in overall health performance of dairy animals, and conversely, imbalance of the microbiota may lead to metabolic diseases. Probiotics have the capability to manipulate the balance/function of the gut microbes resultantly gives a beneficial effect to the host animal. The study aimed to evaluate the effect of commercial versus indigenously isolated strains of Saccharomyces cerevisiae as probiotics on nutrient digestibility, blood chemistry, fecal microbiota, milk production and milk composition of lactating dairy cattle. Two strains of S. cerevisiae (SCQAU03 and SCQAU05) were isolated from cattle dung and fermented food respectively. In the preliminary screening QAU03 shown comparatively higher enzymatic and probiotic potential under mimic rumen gastric conditions. Therefore, was selected for further supplementation in cattle feed. Nine lactating dairy cows were randomly divided into three equal groups. In Group I (served as control group; CON), lactating cows were fed 3 kg concentrate feed, 8 kg silage and 20 kg fodder as control diet. In group II, lactating cows were fed control diet plus commercially (COM) available yeast, while in group III, lactating cows were fed control diet plus laboratory (LAB) produced yeast, for 60 days. Results revealed that neutral detergent fiber and acid detergent fiber digestibility were significantly (p≤0.05) better in LAB fed group (group III) as compared to other groups. LAB fed cows produced significantly (P≤0.05) more milk with higher fat contents. The outcomes of the ruminal gut microflora showed that the average, Lactococcusspecies (CFU/g) counts were increased (p≤0.05) while Enterococcus and coliformssp. (CFU/g) counts were (p≤0.05) decreased in LAB yeast fed groups than other groups which leads to improved GIT microbial balance. It can be concluded that indigenous isolated strain has ability to modulate the GI microbial balance resultantly give an enhancing effect on milk production and milk fat contents in lactating cows.
Keywords: dairy cattle; digestibility; probiotics; milk composition; fecal flora